BOTRIK (ECOBRICK BOTTLES): FROM PLASTIC TO AESTHETIC INNOVATION ECOBRIKS FOR SUSTAINABLE FIELD DECORATIONS: BOTRIK (BOTOL ECOBRIK): DARI PLASTIK JADI ESTETIK INOVASI ECOBRICK UNTUK HIASAN LAPANGAN YANG BERKELANJUTAN - Arshy Prodyanatasari; Djembor Sugeng Walujo; Putu Daneswara Widodo; Sabrina Saskia Eka Nova; Rossita Rachmania; Firliandinurisma Serliana Pramesti (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2026)
The accumulation of non-biodegradable plastic waste in Temporary Storage Sites (TPS) is a critical issue across various regions, including Wates Village, Kediri Regency. The actively operating TPS has not been optimized for advanced management of plastic waste, thereby posing a potential environmental pollution risk. This Community Service (PkM) program aims to address this problem by innovating BOTRIK (Ecobrick Bottles) as aesthetic, sustainable field decorations. The implementation method includes four stages: (1) licensing and coordination with stakeholders; (2) preparation of materials and tools; (3) execution, consisting of collection, sorting, washing, and ecobrick production; and (4) participatory evaluation. The program involved 23 KKN students, the village government, TPS managers, and local community members. As a result, over 55 kg of plastic waste was successfully processed into approximately 175 ecobricks, which were then assembled into two permanent field decoration units in floral and geometric shapes. The impacts achieved include a significant reduction in plastic waste volume at the TPS, increased community capacity in waste management, and the creation of new aesthetic value in public spaces. The BOTRIK program not only demonstrates the effectiveness of ecobricks as a community-based waste solution but also offers a replicable model for other regions. Program sustainability is recommended through the integration of village policies, the establishment of a dedicated waste bank, and the diversification of ecobrick products with economic value.